The performance of an aerated stirred tank reactor on VHG batch fermentations - Raposo, Sara (2014)
The quest for new and renewable energy sources has greatly increased due to the depletion of fossil fuels reserves. Agro-food wastes appear as a cheap and renewable energy source that can contain great amounts of carbon to be transformed in bioethanol that can be used as additive to gasoline.